Inelastic Raman scattering of light by hydrogenlike ions - Jahrsetz, Thorsten; Fritzsche, Stephan; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2014)
The inelastic Raman scattering of light by hydrogenlike ions has been studied by means of second-order perturbation theory and the relativistic Coulomb Green's-function approach. In particular, we investigate the total and angle-differential Raman cross sections as well as the magnetic sublevel population of the residual (excited) ions. Detailed calculations are performed for the inelastic scattering of photons by neutral hydrogen as well as hydrogenlike xenon and uranium ions, accompanied by the 1s1/2→2s1/2, 1s1/2→2p1/2, and 1s1/2→2p3/2 transitions. Moreover, we discuss how the Raman scattering is affected by relativistic and resonance effects as well as the higher-multipole contributions to the electron-photon interaction.